Evaluating responses by pronghorn to fence modifications across the Northern Great Plains - Paul F. Jones; Andrew F. Jakes; Daniel R. Eacker; Blair C. Seward; Mark Hebblewhite; Brian H. Martin (Wildlife Society Bulletin)
ABSTRACT Pronghorn (Antilocapra americana) is an endemic North American ungulate susceptible to negative effects of fences, especially given the vast amount of barbed‐wire fencing currently on the landscape. Despite multiple nongovernmental organizations, and state and provincial wildlife agencies publishing guidelines for creating wildlife‐friendly fencing, there are no published studies that evaluate and compare evidence of the effectiveness of endorsed practices. We analyzed pronghorn crossing success in Alberta, Canada, and Montana, USA, between 2012 and 2016 in response to fence‐modification treatments to understand 1) differences between bottom wire height at selected versus available fence sites, 2) the change in crossing rates before and after fence modification treatments, 3) the effect of a suite of fence, environmental, and demographic characteristics on group crossing success, and 4) the time lag until pronghorn became habituated to different fence modifications after initiation of treatments. Use of either smooth wire or clips with a bottom wire height of approximately 46 cm were most effective at allowing passage by pronghorn, while the commonly proposed goat‐bar was ineffective and created a negative behavioral response by pronghorn. Though smooth wire and clips were effective at allowing passage, we observed a time lag as pronghorn switched use from their strong fidelity at known‐crossing sites to using modified sites. Pronghorn‐group crossing success was greatest during summer, for all‐male groups, and increased with larger group sizes. We advocate not using goat‐bars as modifications to fences, and instead, recommend using smooth wire and clips at a minimum bottom‐wire height of 46 cm to allow movement by pronghorn. Our study provides guidance for wildlife‐friendly fencing techniques to wildlife managers and private landholders as a means to improve permeability for pronghorn and additionally, can be used as a model to evaluate fence modifications for pronghorn and other target species that may be sensitive to fence interactions. © 2018 The Authors. Wildlife Society Bulletin Published by Wiley Periodicals, Inc.